2002
DOI: 10.1105/tpc.000877
|View full text |Cite
|
Sign up to set email alerts
|

Contrapuntal Networks of Gene Expression during Arabidopsis Seed Filling[W]

Abstract: We have used cDNA microarrays to examine changes in gene expression during Arabidopsis seed development and to compare wild-type and mutant wrinkled1 ( wri1 ) seeds that have an 80% reduction in oil. Between 5 and 13 days after flowering, a period preceding and including the major accumulation of storage oils and proteins, ‫ف‬ 35% of the genes represented on the array changed at least twofold, but a larger fraction (65%) showed little or no change in expression. Genes whose expression changed most tended to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
555
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 519 publications
(622 citation statements)
references
References 49 publications
63
555
1
3
Order By: Relevance
“…Transcriptional profiling of oil palm mesocarp revealed Ͼ50-fold higher WRI1 expression levels compared with date palm mesocarp, a closely related species that contains no oil (13). Consistent with data in developing seeds (14), genes encoding machinery for FA biosynthesis and pyruvate supply are up-regulated substantially in oil palm (an average of Ͼ13-fold) (15). The direct precursor of carbon for FA synthesis is pyruvate in most oil-synthesizing tissues, and a plastidial pyruvate dehydrogenase (PDH) supplies acetyl-CoA for ACCase.…”
Section: Regulation Of Fatty Acid Supply By Plastidssupporting
confidence: 80%
“…Transcriptional profiling of oil palm mesocarp revealed Ͼ50-fold higher WRI1 expression levels compared with date palm mesocarp, a closely related species that contains no oil (13). Consistent with data in developing seeds (14), genes encoding machinery for FA biosynthesis and pyruvate supply are up-regulated substantially in oil palm (an average of Ͼ13-fold) (15). The direct precursor of carbon for FA synthesis is pyruvate in most oil-synthesizing tissues, and a plastidial pyruvate dehydrogenase (PDH) supplies acetyl-CoA for ACCase.…”
Section: Regulation Of Fatty Acid Supply By Plastidssupporting
confidence: 80%
“…Changes in transcript abundance in seeds during 5 to 13 d after flowering were recently reported by Ruuska et al (2002). Twenty-six AtPEM candidates changed more than 2-fold during this period (data not shown).…”
Section: Microarray Analysissupporting
confidence: 68%
“…To further investigate the tissue-specific gene expression pattern of AtPEM candidates, we analyzed publicly available cDNA microarray data from the Stanford Microarray Database (SMD; http://genomewww.stanford.edu/microarray; Sherlock et al, 2001) and from the Arabidopsis developing seed array Web site (http://www.bpp.msu.edu/Seed/SeedArray.htm; Girke et al, 2000;Ruuska et al, 2002). Expression profiles of 230 AtPEM candidates for about 110 different microarray experiments were found in the SMD public domain (as of March 12, 2002).…”
Section: Microarray Analysismentioning
confidence: 99%
“…This is suggested by the fact that during embryo development of B. napus embryos, the Suc to hexose ratio in the endosperm liquid increases (see Table I; King et al, 1997). With the increase of Suc concentration in the endosperm liquid and the onset of storage product accumulation, induction of Suc synthase is reported in seeds of B. napus (King et al, 1997) and induction of Suc synthase mRNA and a Suc transporter mRNA are observed in seeds of Arabidopsis (Ruuska et al, 2002). Thus, the relative ratio of uptake of [U-13 C 6 ]Glc and Suc may change during embryo development.…”
Section: Inhomogeneous Distribution Of 13 C Label In Fatty Acids and mentioning
confidence: 94%